Analysis of the Influence of Comorbid States on COVID-19 Severity and In-Hospital Mortality for Further Application in an Outpatient Setting - A. Kurakh; I. Chopey; K. Hechko (Львівський клінічний вісник)
Introduction. The COVID-19 pandemic brought many challenges to the healthcare systems of all countries. Primary care physicians were on the front-lines, handling outpatient care, performing triage, consulting patients on potential risks, symptoms of concern and treatments options. And although emergency and intensive care units have been using severity scales like the quick COVID-19 severity index, Brescia-COVID Respiratory Severity Scale to rapid asses patient severity and adjust care accordingly, these metrics only apply for an inpatient setting and don’t provide much use for outpatient care and management. By isolating main risk factors for developing severe COVID-19, a tool like this can be created for quick evaluation in an outpatient setting.